Do birds of a feather flock together? Factors for religious heterogamy - Fieder, Martin; Schahbasi, Alexander; Huber, Susanne (Journal of Biosocial Science, 2020)
Social cohesion - particularly with regard to the integration of migrants - is primarily measured in terms of education, labour market participation, unemployment, income levels and poverty. When seen from a historical long-term perspective (considering the migrations of Homo sapiens in the past 300,000 years) admixture merged members of diverse groups and forged - in addition to social ties - 'strong biological ties' of kinship, proposing that religious heterogamy is a long-term layer of social cohesion. Accordingly, this study investigated, on the basis of more than 600,000 men and women aged 26-35 years from Austria 2001, Germany (West) 1987, Ireland 2011, Portugal 2011, Romania 2011 and Switzerland 2000, which demographic characteristics foster religious heterogamy, controlling for various confounding factors using linear mixed modelling. By far the most important factor explaining religious heterogamy was the share of adherents to an individual's religious group in their area of residence. It can be concluded that the rate of intermarriage declines with the increasing size of an individual's religious group in their area of residence. From a long-term perspective the lack of familial ties (and conjoint offspring) between religious groups could lead to a lack of social cohesion.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Marriage; Religion; Social Cohesion

Factors affecting attitudes toward migrants—An evolutionary approach - Schahbasi, Alexander; Huber, Susanne; Fieder, Martin (American Journal of Human Biology, 2020)
Objective: To understand migration from an evolutionary perspective, this phenomenon has so far been mainly investigated in animal species. We therefore aim to investigate the potential evolutionary roots of attitudes toward migrants in humans. Methods: We used data from the European Social Survey (n = 83 734), analyzing attitudes toward migrants by performing ordinal mixed models. Results: We found that men have a more restrictive attitude toward migration than women, which increases with age and is stronger with a child in the household. Attitude toward migrants is also more skeptical if migrants have a different ethnicity and are from poorer countries. Increasing education and religiousness are associated with a more positive attitude toward migrants, particularly toward migrants of different ethnicity and from poorer countries. Discussion: Although migration flows are a hallmark of the human species, previous findings suggest that (pre-)historic migration flows were at times accompanied by conflict and violence, while at the same time, they insured survival by allowing cultural exchange and the avoidance of inbreeding. Accordingly, we assume that contemporary attitudes toward migration are rooted in our evolutionary past. We discuss the respective behavioral patterns from an evolutionary perspective, arguing that both—a negative attitude as well as openness—make sense.
CRIS-Team Scopus Importer:2020-06-05

Marriage in the Melting Pot: An Evolutionary Approach to European Ancestry, Homogamy, and Fertility in the United States - Schahbasi, Alexander; Huber, Susanne; Fieder, Martin (Frontiers in Psychology, 2022)
To understand marriage patterns, homogamy, and fertility of women of European ancestry in the United States from an evolutionary perspective, we investigated if a prevalence of ancestral homogamy exists, the factors influencing a female preference for an ancestral homogamous vs. heterogamous marriage, and if ancestral homogamous vs. heterogamous marriages have an impact on fertility. Furthermore, we aim to determine the heritability of homogamous vs. heterogamous marriage behavior. We used the census data of 369,121 women in the United States married only once and aged between 46 and 60 years, provided by IPUMS USA (https://usa.ipums.org/usa/). We used linear mixed models to determine the association between the probability of a homogamous vs. heterogamous marriage and the individual fertility of women. We aimed to estimate the heritability (genetics and parental environment) of marriage behavior using a linear mixed model. We found that ancestral heterogamous marriages are more frequent compared to homogamous marriages, but only if all ancestry groups are included. If ancestry is aggregated, homogamous marriages are more frequent compared to heterogamous marriages. Most of the variance (up to 27%) in inter-ancestry marriage and fertility (up to 12%) is explained by ancestry per se, followed by the ratio of individuals of a certain ancestral background in a county (∼6%), indicating a frequency depending selection into marriage: the more individuals of a certain ancestry live in a county, the lower is the tendency to marry someone of a different ancestral background. Furthermore, we found that about 12% (depending to some extent on the clustering) of the marriage behavior is heritable. Being in a homogamous marriage and the income of the spouse are both significantly positively associated with the number of children women have and the probability that women have at least one child, albeit explaining only a very low proportion of the overall variance. The most important factor (in terms of variance explained) for being in an ancestral homogamous vs. heterogamous marriage, for the number of children, and for childlessness is the ancestry of the women. Most children are born to women of Irish, French, and Norwegian ancestry (Irish X̄: 3.24, French X̄: 3.21, and Norwegian X̄: 3.18), the lowest number of children is to women of Latvian, Rumanian, and Russian ancestry (Latvian X̄: 2.26, Rumanian X̄: 2.19, and Russian X̄: 2.35). Albeit, we are not able to distinguish the genetic and social heritability on the basis of our data, only a small heritability for in-group vs. out-group marriage behavior is indicated (∼12% of variance explained).
CRIS-Team Scopus Importer:2022-08-05
Keywords: evolution; fertility; heritability; homogamy; marriage; social cohesion